Answer:
y = -3/4x - 6
Step-by-step explanation:
Answer:
J: x - 2y = -8
Step-by-step explanation:
All you have to do is plug in x or y as 0 for the y-intercept and the x-intercept, respectively. But, for these specific equations, looking at the constant when y isn't multiplied by any number but 1 will show the y-intercept. (e.g. 2x + y = -12, -12 is the y-intercept, 2x - y = -20 -> -2x + y = 20, 20 is the y-intercept)
F: y-intercept = -12 (incorrect)
G: y-intercept = 0 (incorrect)
H: y-intercept = 20 (incorrect)
J: y-intercept = 4 (correct)
Answer:
A)
Step-by-step explanation:
Given expression:
To factor the given expression completely.
Solution:
In order to factor the expression, we will factor in pairs.
We will factor the G.C.F of the terms in the pairs.
G.C.F. of and can be given as:
Thus, G.C.F. =
G.C.F. of and can be given as:
Thus, G.C.F. =
The expression after factoring the G.C.F. pairs is given as:
Taking G.C.F. of the whole expression as is a common term.
The expression is completely factored.
Step-by-step explanation:
Answer:
700 minutes or 11.67 hours
Step-by-step explanation:
35/4=8.75
8.75*80=700
Answer:
$1.5 per shirt if that's what you meant
Step-by-step explanation: